2016
DOI: 10.3171/2015.6.jns1519
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter prospective cohort study of volume management after subarachnoid hemorrhage: circulatory characteristics of pulmonary edema after subarachnoid hemorrhage

Abstract: S ubarachnoid hemorrhage (SAH) from a ruptured aneurysm is accompanied by several complications, including electrolyte abnormalities, vasospasm, hydrocephalus, cardiac dysfunction, and pulmonary edema. 15,16,18 Among these complications, delayed cerebral ischemia (DCI) remains an important cause of morbidity and death. 15 Many studies have investigated the prevention or treatment of DCI after SAH.Triple-H therapy (i.e., hypertension, hypervolemia, and hemodilution) has reportedly been an effective approach abb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“… 2 Early and aggressive surgery or intervention reduces morbidity and mortality. 3 In addition, SAH is also complicated with fever and pulmonary changes, 4 , 5 which need to be differentiated from COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Early and aggressive surgery or intervention reduces morbidity and mortality. 3 In addition, SAH is also complicated with fever and pulmonary changes, 4 , 5 which need to be differentiated from COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of extravascular lung water index, cardiac index, and pulmonary vascular permeability index with Pulse Contour Cardiac Output (PiCCO) is considered to be useful in the identification of pulmonary edema in SAH patients [78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95]. Neither statin therapy nor magnesium infusions should be initiated for delayed cerebral ischemia.…”
Section: Complications and Current Treatment Approachesmentioning
confidence: 99%
“…Ref. [12] used the Pulse Contour Cardiac Output Catheter (PiCCO) monitoring system to track a lung fluid index, which was higher in patient diagnosed with pulmonary edema.…”
Section: Defining Volume Statusmentioning
confidence: 99%
“…The PiCCO catheter system is an interesting intermediate (recently reviewed in [26]). A series of studies [12,27,28] have shown that PiCCO-derived global end diastolic index (GEDI) and CO were predictive of pulmonary edema and heart failure in SAH patients. These studies are a major step forward in establishing the predictive validity of the PiCCO monitoring system for SAH patients.…”
Section: Targeting Fluid Therapymentioning
confidence: 99%